SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU ( PPDB ) DI MA SABDA RIA NADA SUMBERMALANG - Erfandi Agusti Kiki Wahyono; Rahmat Shofan Razaki; Firman Jaya (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
Information System for New Student Admissions (PPDB) at MA Sabda Ria Nada. Information Technology Education, Teacher TrainingCollegeand Education Science Teacher Association of the Republic of indonesia. This information system includes the New Student Admissions (PPDB) activity which will allow prospective new students to register at MA Sabda Ria Nada without having to come to school to register. The new student admissions information system software at MA Sabda Ria Nada was successfully created using PHP and MySQL. This system is able to manage registration well. In this study the authors used a research and development type or Research and Development (R & D).Based on the perception of the media expert, it is 100% very feasible, the assessment by the material expert is 90% very feasible and the assessment from 4 users states 80% is feasible and 20% states it is not feasible. Information System for New Student Admissions (PPDB) at MA Sabda Ria Nada. Information Technology Education, Teacher TrainingCollegeand Education Science Teacher Association of the Republic of indonesia. This information system includes the New Student Admissions (PPDB) activity which will allow prospective new students to register at MA Sabda Ria Nada without having to come to school to register. The new student admissions information system software at MA Sabda Ria Nada was successfully created using PHP and MySQL. This system is able to manage registration well. In this study the authors used a research and development type or Research and Development (R & D).Based on the perception of the media expert, it is 100% very feasible, the assessment by the material expert is 90% very feasible and the assessment from 4 users states 80% is feasible and 20% states it is not feasible.